(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Guidelines presented herein are a refinement over theCorporate Social Responsibility Voluntary Guidelines 2009, released by theMinistry of Corporate Affairs in December 2009. Significant inputs, receivedfrom diverse stakeholder groups across the country have been duly considered,and based on these inputs; appropriate changes have been made in the originaldraft Guidelines produced by the Guidelines Drafting Committee. This documenttherefore represents the consolidated perspective of vital stakeholders inIndia, and accordingly lays down the basic requirements for businesses tofunction responsibly, thereby ensuring a wholesome and inclusive process ofeconomic growth.